"Laudato Si'" and the Environmental Imperative: a Compelling Theology for our Times? - Williams, Stephen N. (European journal of theology, 2019)
The Papal Encyclical Laudato Si' approaches environmental questions by offering a synthesis of faith and reason. Acknowledging the range of responses which Laudato Si' has received, this article tries to adopt an independent approach to the encyclical. After describing the synthesis, it argues that it is not entirely persuasive because the encyclical does not show enough awareness of rational objections that are brought against the Christian understanding of creation and of eschatology. This weakens the argument of the encyclical on its own terms. The article also raises questions about both Laudato Si's emphasis on personified language to describe the world and its panentheism. We can value and care for the natural world without describing the relationship of God to the world in the terms of Laudato Si'. However, these criticisms are placed in a context of warm appreciation for the encyclical and an exhortation for us to take the personal example of Francis of Assisi seriously. (English)